Electrical properties of fractal nanofilms of porous silicon - Zhanabaev, Z.Zh.; Ibraimov, M.K.; Sagidolda, E. (Publishing House of the KarSU named after E.A.Buketov, 2013)
Samples of porous silicon films grown by electrochemical etching have been investigated. Morphology of the films has been studied by use of scanning probe microscope NTegra Therma. We established that electrical properties of thin films of porous silicon are strongly influenced by various factors such as strength of current through a film, etc. Current-voltage characteristic of the porous silicon films has a strong non-linear and chaotic region in a certain range of voltage. Dependence of current on voltage corresponding to multiple electron tunneling can be used for development of generators of chaos with a broadband spectrum.
Keywords: electrical properties; fractal nanofilms; porous silicon film; microscopy; current-voltage characteristics